2000
DOI: 10.1063/1.126903
|View full text |Cite
|
Sign up to set email alerts
|

Photon scanning tunneling microscopy of tailor-made photonic structures

Abstract: Optical field distributions around individually fabricated subwavelength scatterers mapped with a photon scanning tunneling microscope are presented. The photonic structures are produced from ridge waveguides using focused-ion-beam milling. This flexible technique allows us to make single holes and slits of sizes down to 30 nm. A quantitative analysis of the observed optical pattern due to interference between incoming and reflected light yields insight about subwavelength scatterers in waveguides. We conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…In all measurements discussed in this paper, coated fiber probes with aperture diameters of 80 nm were used. Previous investigations on strongly scattering structures showed that scattered light emanating from the structure can couple directly into the fiber probe [35] swamping the signal originating from the light propagating inside the structure. Local probing of field intensities with uncoated fiber probes therefore becomes impossible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all measurements discussed in this paper, coated fiber probes with aperture diameters of 80 nm were used. Previous investigations on strongly scattering structures showed that scattered light emanating from the structure can couple directly into the fiber probe [35] swamping the signal originating from the light propagating inside the structure. Local probing of field intensities with uncoated fiber probes therefore becomes impossible.…”
Section: Methodsmentioning
confidence: 99%
“…Excitation of "leaky modes" can lead to a number of different discrete -vectors being present in the reflected light. "Leaky modes" are high loss modes, which are not supported by the waveguide geometry [35]. If scattering of light at the air rods excites leaky modes, an interference pattern with a fast exponential decay in front of the air rods is expected.…”
Section: Optical Intensity Distributions Of Lightmentioning
confidence: 99%
“…Furthermore, the heterodyne mixing yields enhancement of signal and dynamic range. This heterodyne interferometric method will give detailed information on the operation of many (novel) photonic structures: phasars [1], [2], MMIs [3], [4], microcavities [9], [10], photonic crystals [6]- [8], etc., in which the phase of light is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…For all photonic structures based on inter-ference, like phasars, MMIs, microcavities, and photonic crystals, determining the phase evolution of light inside the structure is crucial. In the case of microcavities [9], [10] and photonic crystals [6]- [8], the optical amplitude of the light inside the structures has been measured as a function of position (lateral resolution 50 nm) with a PSTM [9], [10], but the direct measurement of the phase is yet lacking. A number of theoretical papers have presented algebraic formulas that describe the phase of the output channels of phasars [1] and MMIs [13].…”
mentioning
confidence: 99%
“…All these effects lead to attenuation of light, which makes the fabrication of low-loss photonic components difficult. FIB has been used to study various phenomena involving light in waveguides [2], [3] and allows the direct fabrication of structures such as photonic crystals [4], [5]. But to our knowledge there are few or no reports in literature about low-loss photonic devices fabricated in siliconon-insulator by means of FIB.…”
mentioning
confidence: 99%